What is the optimal In2Care stations density to achieve Aedes aegypti population reduction in a dengue endemic setting? - Welington Tristão; Murilo Reis; Pedro G G Moraes; Lara H Pires-Vieira; André S Leandro; Wagner A Chiba de Castro; Rafael Maciel-de-Freitas (PLoS Neglected Tropical Diseases)
Background Autodissemination traps are among the most innovative strategies for suppressing mosquito vector populations. These traps are particularly effective against Aedes aegypti due to the species' skip oviposition behavior, where eggs from a single clutch are distributed across multiple breeding sites. Evaluating the efficacy of different densities of In2Care stations under large-scale field conditions is crucial for understanding their potential impact on Ae. aegypti populations. Methodology/principal findings A total of 3,250 In2Care stations were deployed in Goiânia, the 10th largest city in Brazil, with an estimated population of 1.45 million. The field study lasted 14 months, with each station serviced bi-monthly. To assess the impact of In2Care, ovitraps were installed and inspected weekly to measure changes in the number of positive ovitraps and the average number of eggs laid by Ae. aegypti females in intervention areas compared to control neighborhoods. Over the course of the study, 666,204 eggs were sampled. The density of In2Care stations varied across neighborhoods, ranging from 220 to 555 stations per km2. In the high-density area (~555 stations per km2), the Ovitrap Positivity Index (OPI) decreased from 56.9% to 31.5%, while the average number of eggs per positive paddle dropped from 41.2 to 18.1-representing a 56% reduction in egg counts. Conversely, in the low- and medium-density, no significant effect was observed. Conclusions/significance The recommended density of In2Care is about 2500 stations per Km2. Our results demonstrated stations density 4.5 times lower than the recommended density is able to reduce the frequency of positive ovitraps and the number of eggs collected on them. entomological indexes. Additional fieldwork in other entomological and epidemiological settings are needed to evaluate whether the In2Care density of ~555 units/Km2 observed for Goiânia was site-dependent or if it has borader applicability. Our results show that In2Care stations can effectively suppress Ae. aegypti populations over large geographic areas, with efficacy likely influenced by trap density.